Health-related quality of life and its associated factors among Type 2 Diabetes Mellitus patients attending health clinics in Tampin district, Negeri Sembilan, Malaysia - Basir, Nur Fadhilah (2016)
Introduction: Diabetes Mellitus is one of the common non-communicable diseases in nearly all countries. It has an impact on quality of life, given by their lifelong nature and the need for self-management. In a chronic disease as Type 2 Diabetes Mellitus, health-related quality of life (HRQOL) is an important outcome measure, as a patients’ perception about the disease and does not depend on the clinical parameters only. The Short Form 36 (SF-36) is an established HRQOL survey questionnaire for health outcome measurement. The aim of this study was to determine the HRQOL and its associated factors among Type 2 Diabetes Mellitus patients attending health clinics at the district of Tampin, Negeri Sembilan. Methodology: A cross-sectional study applying the Malay version of SF-36 and a structured pretested questionnaire among Type 2 Diabetes Mellitus patients attending all five health clinics at district of Tampin, Negeri Sembilan. All Type 2 Diabetes Mellitus patients who registered and received treatments at all five health clinics and met the inclusion criteria were taken as sample. Respondents were selected using stratified sampling method from each clinic. Demographic data, clinical characteristics, self-care behavioural factors and the Malay version of SF-36 questionnaire was administered by face-to-face interview. A total 430 respondents with 99.5% response rate were analysed. Descriptive analysis, t-test, Pearson product-moment correlation coefficient, ANOVA and hierarchical linear regressions analysis were applied to the data using SPSS version 21.0 software. Results: Majority of the respondents were females (54.2%), Malay (72.3%), married (83%), and attended primary education (58.1%).The mean age of the respondents was 57.5(±8.88) years and the mean duration of having diabetes was 6.9 (±5.01) years. About 40.9% were overweight, and more than half had uncontrolled diabetes (HbA1c ≥6.5%). Mean score of SF-36 health domains with exception of role emotional of respondents were significantly lower than that of the Malaysian norm scoring by Azman (2003) (P<0.001). Further analysis in hierarchical regression analysis revealed that, older age (P<0.001), Indian ethnic (P<0.05), household income (P<0.05), combination of oral hypoglycemic agents (OHA) and insulin treatments (P<0.01), years of having diabetes (P<0.05), having more than two co-morbidities (P<0.05), selfmonitoring blood glucose (P<0.05), and uncontrolled glycemic status (HbA1c≥6.5%) (P<0.05) are the factors associated with deterioration of HRQOL among respondents. Conclusion: Type 2 Diabetes Mellitus was associated with lower HRQOL in comparison to normal population. HRQOL was significantly associated with sociodemographics, clinical and self-care behavioural factors of patients in district of Tampin. In the clinical settings, this knowledge can be used to encourage medical professionals to actively identify patients’ difficulties in managing diabetes during routine diabetic follow-up consultations. This practice could promote in early detection of any reduced HRQOL. Both physical and mental aspects should be considered into and interventions are planned accordingly, efforts to improve the patients’ health via individualized programme may alleviate the overall HRQOL.